Mechanical activation of the solid-phase reaction between bismuth citrate and iron(II) oxalate dihydrate to yield BiFeO3. Issue 5 (June 2015) - Berbenni, Vittorio; Milanese, Chiara; Bruni, Giovanna; Girella, Alessandro; Marini, Amedeo
Abstract : Abstract: The work deals with the synthesis of multiferroic BiFeO3 starting from mixture of Bi citrate and Fe(II) oxalate dihydrate. By combined TG-DSC and XRPD experiments it is put into evidence that the mechanically activated mixture absorbs an extra enthalpy (+235 kJ) that is due to the reaction between the forming oxides. Furthermore it is shown that mechanical activation of the starting mixture sensibly enhances the formation of Bi ferrite. Indeed BiFeO3 is obtained by annealing the activated mixture at temperatures as low as 750 °C while this does not happen by annealing the physical mixture at temperatures up to 800 °C. Finally by MTDSC (Modulated Temperature Differential Scanning Calorimetry) we measured the thermal capacity of BiFeO3 obtained from the annealed activated mixture.